Design of Rainwater Harvesting System for Sustainable Urban Development - Pratama, Hendri; Rahman, Ataur; Sánchez, Edith Rosalba Salcedo (RESWARA: Jurnal Riset Ilmu Teknik, 2024)
Rapid urbanization has intensified pressure on conventional water supply systems while simultaneously increasing surface runoff and flood risks in urban areas. Rainwater Harvesting Systems (RHS) have emerged as a strategic solution to enhance urban water security and promote sustainable development. This study aims to analyze and synthesize design principles of urban rainwater harvesting systems based on recent empirical studies, modeling approaches, and real-world case applications. A systematic literature-based research method was employed, integrating comparative analysis of system components, design criteria, optimization techniques, and performance indicators reported in international peer-reviewed journals. The results demonstrate that well-designed RHS can reduce potable water demand by 25–90%, mitigate urban flooding, and enhance stormwater management efficiency when integrated with Sustainable Urban Drainage Systems (SUDS). Key findings emphasize the importance of site-specific rainfall patterns, storage capacity optimization, socio-economic considerations, and technological integration such as GIS, BIM, and stochastic optimization models. The study concludes that rainwater harvesting systems, when properly designed and implemented, represent a resilient and cost-effective approach to sustainable urban water management, particularly in water-stressed and rapidly urbanizing regions.